Logistic Quality Management of Transport Process in Construction - Zelinska, Halyna; Boldyrieva, Lyudmyla; Amelina, Iryna (International Journal of Engineering and Technology, 2018)
The article presents the key problems of the logistics management of the quality of the transport process in the construction industry. Characterized by the influence transport services quality on the efficiency of production and commercial activate enterprise. The main indicators of quality of transportation are summarized: qualitative indicators; indicators assessing the effect of transportation of construction materials in due time; indicators characterizing loss of product during transportation. The technological scheme of goods transportation by the means of transport (with quality control of the transport process) is presented. The directions of quality assurance of transport provision are offered: formation of material and technical basis of transport; creation of preconditions for efficient use of transport; improvement of organizational and economic mechanism of transport-logistic systems functioning. The allowed limits of different types use transport on the criterion of productivity or cost of transportation are offered. It was established that the essential reserve for improving the efficiency of transport and technological processes in construction (along with increasing the throughput and improving the quality of machines operation) is to: improve transport equipment of transport complexes; application of the newest technologies of transport processes; the use of effective ways to manage transport robots. The basic reserve of reduction of specific energy consumption on motor transport is determined. The main ways of reducing specific fuel consumption during transportation are given. The main directions of rolling stock fuel economy are increase formulated. The measures of loading and unloading works of labor-intensity execution reduction are substantiated.Â Â